So happy together: juvenile crabeater seal behavior improves lice transmission - Soto, Florencia Anabella; Klaich, Matias Javier; Negrete, Javier; Leonardi, María Soledad (Parasitology Research)
Lice from family Echinophthiriidae are of the few insects that have successfully colonized marine environment living as ectoparasites of pinnipeds, i.e., sea lions, seals, and the walrus. They have developed unique adaptations to cope with the amphibious lifestyle of their hosts. Because eggs do not survive underwater, lice could only reproduce when their host remains on pack ice enough time. Consequently, lice generations per year are limited by host haul-out behavior. The objective of this work is to study the effect of host sex and age class, and the annual variation on the prevalence and mean abundance of Antarctophthirus lobodontis in crabeater seals from the Antarctic Peninsula. During three consecutive field-seasons, we collected lice from 41 crabeater seals (23 females, 16 males, 2 indeterminate, being 24 adults, and 17 juveniles). We investigated this effect on the prevalence and mean abundance by a generalized linear model formulation in a Bayesian framework. According to the lowest Deviance Index Criterion model, sex host does not affect prevalence nor mean abundance. We found that juveniles present greater abundance and prevalence than adults, possibly due to foraging habits. They spent more time on the ice than adults in groups of dozens of animals. This behavior would favor both egg development and lice transmission. We do not find adult females with lice, which suggests that transmission of A. lobodontis should be horizontal. The high mean abundance of lice in 2014 could be associated with an unusual increase in Lobodon carcinophaga population, probably related to the pack-ice availability and zooplankton abundance. Fil: Soto, Florencia Anabella. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Instituto de Biología de Organismos Marinos; Argentina Fil: Klaich, Matias Javier. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: ...